Reflection and an Appetite for Experience: Theory to Classroom Practice - Judith Halden-Sullivan (Journal of the Assembly for Expanded Perspectives on Learning, 1998)
Reflection promotes an openness to thinking and an appetite for experience that must ground everyday classroom practice.